Video demystified a handbook for the digital engineer - Jack, Keith, 1955- (Amsterdam ; Boston : Newnes/Elsevier, 2007)
Covers digital video formats - Blu-ray and HD-DVD, development of audio and video codecs - Dolby Digital Plus, DTS-HD, etc along with the information on HDTV, HDMI and IPTV (TV over the Internet). This book helps in the design of devices and infrastructures from analog to digital television transmission.
Front Cover; Video Demystified: A Handbook for the Digital Engineer; Copyright Page; Contents; About the Author; Chapter 1. Introduction; Chapter 2. Introduction to Video; Chapter 3. Color Spaces; Chapter 4. Video Signals Overview; Chapter 5. Analog Video Interfaces; Chapter 6. Digital Video Interfaces; Chapter 7. Digital Video Processing; Chapter 8. NTSC, PAL, and SECAM Overview; Chapter 9. NTSC and PAL Digital Encoding and Decoding; Chapter 10. H.261 and H.263; Chapter 11. Consumer DV; Chapter 12. MPEG-1; Chapter 13. MPEG-2; Chapter 14. MPEG-4 and H.264; Chapter 15. ATSC Digital Television
Keywords: Television -- Handbooks, manuals, etc; Digital video -- Handbooks, manuals, etc; Electronic books